1989
DOI: 10.1038/339383a0
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-2 production used to detect antigenic peptide recognition by T-helper lymphocytes from asymptomatic HIV-seropositive individuals

Abstract: T lymphocytes from mice and healthy humans immunized against the human immunodeficiency virus (HIV) envelope have recently been shown to recognize two antigenic regions of the gp160 HIV-envelope protein which have been located on the basis of amphipathicity. In HIV-infected humans, T-cell proliferative responses are lost soon after infection. Here we demonstrate that interleukin-2 production is often retained even when proliferative activity is absent, and that it can be used to monitor T-helper cell responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
1
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 205 publications
(89 citation statements)
references
References 11 publications
2
84
1
1
Order By: Relevance
“…This greatly contrasted with the early defect in activation of T cells cocultured with Lps-treated Mo͞Mø (20), which could be compensated by increasing the number of ACs or addition of IL-2 (21). The lack of impairment of early events in T cell activation, including calcium flux and phosphotyrosine kinase activity, was observed in the T cells cocultured with HIVinfected ACs (22) or T cells isolated from HIV-infected individuals (1,23), suggesting a similar alteration with respect to accessory function of Tat-ACs and HIV-infected ACs. The partial activation of T cells is believed to be a critical factor for the maintenance of the infectious status, as HIV cannot infect resting T cells.…”
Section: Immunology: Wu and Schlossmanmentioning
confidence: 87%
“…This greatly contrasted with the early defect in activation of T cells cocultured with Lps-treated Mo͞Mø (20), which could be compensated by increasing the number of ACs or addition of IL-2 (21). The lack of impairment of early events in T cell activation, including calcium flux and phosphotyrosine kinase activity, was observed in the T cells cocultured with HIVinfected ACs (22) or T cells isolated from HIV-infected individuals (1,23), suggesting a similar alteration with respect to accessory function of Tat-ACs and HIV-infected ACs. The partial activation of T cells is believed to be a critical factor for the maintenance of the infectious status, as HIV cannot infect resting T cells.…”
Section: Immunology: Wu and Schlossmanmentioning
confidence: 87%
“…Recombinant gp 120 was a generous gift from Genentech (San Francisco, CA). A group of five synthetic peptides corresponding to the env of HIV-1 (T1, T2, Th4.1, P18IIIB, and pl8MN) have been previously described (14,15). Mouse anti-human magnetic beads were purchased from Advanced Magnetic Inc. (Cambridge, MA).…”
Section: Methodsmentioning
confidence: 99%
“…In that study, Converse et al [28] showed a specific deletion of T cells recognizing the major epitopes of CMV, a deletion that was specific for HIV-infected individuals, whereas T cell proliferation in response to minor epitopes remained comparable to controls. Similarly, the response to antigens encountered frequently (like env or influenza) is rapidly lost [29], whereas the response to rarely encountered antigens like allo-MHC antigens [29], or tetanus toxoid (H.G., personal observations) remains for a longer period. This model may also explain the relative heterogeneity of the results obtained in different studies analysing the T cell repertoire of HIV-infected patients [30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%